2013
DOI: 10.11005/jbm.2013.20.2.105
|View full text |Cite
|
Sign up to set email alerts
|

Bone Mineral Density Changes after Total Knee Replacement in Women Over the Age of 65

Abstract: BackgroundThere are few reports on bone mineral density (BMD) changes of axial bones after total knee replacement (TKR) due to severe osteoarthritis (OA) of the knee joint and its results are controversial. The purpose of our study was to measure the BMD changes of hip and spine in patients receiving TKR due to severe OA and to identify clinical factors relating BMD changes.MethodsAmong 66 female patients above 65 years old who underwent TKR due to severe OA and checked preoperative BMD, 52 patients who checke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Mintzer et al [ 64 ] reported that within the first 12 months post-operatively, 68% of patients had radiographic evidence of bone loss at the distal anterior femur. There are many more studies that have shown a correlation between TKR (arthroplasty) and BMD loss [ 59 , 65 70 ], although there are some studies that dispute this association and have shown no change in BMD post-TKR/A [ 57 , 71 , 72 ], with some research actually showing a small increase [ 73 ].…”
Section: Bmd Fracture and Tkr Relationshipmentioning
confidence: 99%
See 1 more Smart Citation
“…Mintzer et al [ 64 ] reported that within the first 12 months post-operatively, 68% of patients had radiographic evidence of bone loss at the distal anterior femur. There are many more studies that have shown a correlation between TKR (arthroplasty) and BMD loss [ 59 , 65 70 ], although there are some studies that dispute this association and have shown no change in BMD post-TKR/A [ 57 , 71 , 72 ], with some research actually showing a small increase [ 73 ].…”
Section: Bmd Fracture and Tkr Relationshipmentioning
confidence: 99%
“…One possible intervention is antiresorptive treatment. Hahn and Won [ 72 ] investigated this, concluding that bisphosphate treatment just after TKR surgery prevented early BMD reduction in the hip and would be beneficial in the prevention of later hip fracture. This is supported by research by Carulli et al [ 91 ], who proposed the use of bisphosphonate treatment in patients to not only prevent bone loss but increase implant survival.…”
Section: Bmd Fracture and Tkr Relationshipmentioning
confidence: 99%
“…13,14 In addition, 1 year of bisphosphonate treatment prevents early reduction of hip BMD after THA regardless of osteoporosis diagnosis. 15 In 20,784 primary TKA patients 65 years and older, patients who did not use bisphosphonates had a more than 3 times greater risk of revision than patients who used bisphosphonates and bisphosphonates had a protective effect even for patients with normal BMD postoperatively. 16 Further, several studies suggest that treatment of osteoporosis with bisphosphonates for patients with osteoarthritis may reduce the need for TJR, potentially through n guest editorial antiresorptive effects that minimize periprosthetic bone loss and osteolysis.…”
mentioning
confidence: 99%
“…Clinically, the most common cause leading to revision knee arthroplasty is the aseptic loosening of components [ 6 , 7 ] that occurs when periprosthetic bone is resorbed because of surgeon-related factors such as malalignment, patient-related factors such as bone quality, or implant-related factors such as cemented or cementless fixation or design, among others [ 6 ]. The results of two studies demonstrated that bisphosphonates, which prevent bone resorption, significantly reduce the rate of revision surgery [ 8 ] and increases the T-score hip bone mineral density (BMD) after TKA [ 9 ]. Conversely, several studies did not find any beneficial effects of bisphosphonate treatment [ 10 - 12 ].…”
Section: Introductionmentioning
confidence: 99%